2016
DOI: 10.1080/09540121.2016.1243788
|View full text |Cite
|
Sign up to set email alerts
|

Unmet core needs for self-determination in HIV-infected women of color in medical care

Abstract: The levels of satisfaction of the core self-determination needs (relatedness, autonomy, competence) among HIV-infected women of color as well as the association between need fulfillment and patient characteristics were examined. Having less than a high school education was associated with lowest need satisfaction: autonomy (β= −1.90; 95%CI= −3.20, −0.60), relatedness (β= −2.70; 95%CI= −4.30, −1.10), and competency (β= −2.50; 95%CI= −3.60, −1.30). Each additional point increase in affective symptoms of depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Consistent with other studies, 33,44-48 we found that many participants experienced HIV diagnosis as a traumatic stressor and reacted to their HIV diagnosis with difficulties cognitively processing any HIV education provided while incarcerated, 45 as well as with denial 32 and numbing responses such as problematic substance use. 44,46 Receiving an HIV diagnosis can be traumatic and overwhelming in the best of circumstances but incarceration likely worsens this experience due to social isolation, 48 amplified HIV-stigma, 49 loss of autonomy, 50 and substandard medical care. 22 Based on these findings, clinicians who treat PLWH of color who have received an HIV diagnosis while incarcerated should be aware of and have an understanding that an HIV diagnosis can be traumatizing, particularly under the unique circumstances of being diagnosed with HIV while incarcerated.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other studies, 33,44-48 we found that many participants experienced HIV diagnosis as a traumatic stressor and reacted to their HIV diagnosis with difficulties cognitively processing any HIV education provided while incarcerated, 45 as well as with denial 32 and numbing responses such as problematic substance use. 44,46 Receiving an HIV diagnosis can be traumatic and overwhelming in the best of circumstances but incarceration likely worsens this experience due to social isolation, 48 amplified HIV-stigma, 49 loss of autonomy, 50 and substandard medical care. 22 Based on these findings, clinicians who treat PLWH of color who have received an HIV diagnosis while incarcerated should be aware of and have an understanding that an HIV diagnosis can be traumatizing, particularly under the unique circumstances of being diagnosed with HIV while incarcerated.…”
Section: Discussionmentioning
confidence: 99%
“…However, factors such as the convenience and privacy of home-based testing and sexual partners' encouragement and support also played an important role in motivating some men to test. Following engagement with EPIC-HIV1, most men in our sample were able to initiate a new behaviour, such as HIV testing, to achieve positive health outcomes (Quinlivan et al, 2017;. This suggests that offering EPIC-HIV1 with other interventions such as HIV self-testing, and support partner-initiated testing, has the potential to encourage men to exercise their autonomy to test.…”
Section: Discussionmentioning
confidence: 82%
“…EPIC-HIV messaging is rooted in self-determination theory (SDT) to increase men's intrinsic motivation to test (EPIC-HIV1) for HIV. SDT is a behavioural change theory that relies on individual psychological needs for autonomy, competence and relatedness to be internally motivated to adopt a new behaviour (Deci & Flaste, 1995;Quinlivan et al, 2017). Autonomy entails people's ability to make individual decisions associated with their identity, beliefs and values, while competence requires an individual to be able to act Johnson, 2007;Johnston & Finney, 2010;Quinlivan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations